Edukasi Harmoni Pasca Pemilu Desa Kertasura Dan Penyuluhan Pencegahan Perpecahan Melalui Animasi - Fadhil Muhammad Basysyar; Edi Tohidi; Fajrina Putri Salsabila; Adi Kaswadi; Eddiwan Dwiguna (CV. Multi Kreasi Media, 2023)
Elections are important moments in a democratic country, but they can often trigger conflict and division in society. Likewise, social media, such as YouTube, has played an increasingly large role in disseminating political information. Counseling on preventing post-election divisions via YouTube in Kertasura Village is a community service initiative that aims to overcome potential post-election social conflicts. In this situation analysis, we will explore partner locations and cases that have occurred, analyze social and cultural aspects in Kertasura Village. The results of community service regarding socialization media videos to prevent post-election divisions based on explainer animations can increase the sense of tolerance and respect for differences of opinion among millennials. Producing socialization media videos based on explainer animations as a socialization media innovation to prevent division after the election that is acceptable among millennials.